Assessment of highway filter drain fouling and performance considerations - Theo Stylianides; Matthew Frost; Paul Fleming; Ali El-Jaber; Mark Mageean (2015)
The road carriageway and pavement sub-surface of many UK highways are drained by Highway Filter Drains (HFD). These are gravel filled trenches fitted with a porous carrier pipe at the base that convey surface and sub-surface water to an outfall. HFD are typically characterized as free draining upon construction however, over time the voids of the granular medium become filled due to the intrusion of fines washed from the adjacent earthworks or pavement surface. The lack of understanding of the deterioration mechanisms and the absence of a structured fouling characterization limit the assessment of operational and residual HFD life to qualitative or subjective estimation of in-service performance. This extends to maintenance procedures that are predominately reactive. This paper reviews the current state of knowledge of HFD performance and drainage media condition assessment. It then presents a method of fouling characterization based on assessment of samples from in service drains. Three fouling scales are thus suggested; the percentage drain fouling, the foulant-aggregate ratio and the free voids ratio. In-service HFD are found to be functioning at an acceptable standard with a limited number of localized failures attributed to highly fouled layers at the surface of the trench. It is proposed that a rational evaluation of a HFD section should employ means other than just visual indicators. The fouling assessment is linked to laboratory permeability tests conducted with different levels of filter material fouling. It is found that the extent, spreading and type of fouling are important to determine how the filter aggregate performs.